Potential of 6-mm-diameter fully covered self-expandable metal stents for unresectable malignant distal biliary obstruction: a propensity score-matched study - Daiki Yamashige; Susumu Hijioka; Yoshikuni Nagashio; Yuta Maruki; Soma Fukuda; Shin Yagi; Kohei Okamoto; Hidenobu Hara; Yuya Hagiwara; Daiki Agarie; Tetsuro Takasaki; Akihiro Ohba; et al. (Clinical Endoscopy)
Background/Aims To date, only thinner-diameter metal stents have been evaluated for unresectable malignant distal biliary obstruction (UR-MDBO). This study investigated the outcomes and optimal cohorts for a 6-mm-diameter fully covered self-expandable metal stent (FCSEMS) compared with those for a 10-mm-diameter FCSEMS. Methods This single-center retrospective cohort study included patients who underwent initial transpapillary metal stenting for UR-MDBO. Propensity score matching (1:1) analysis was performed. Results Of 133/68 patients who underwent 6-mm/10-mm-diameter FCSEMS deployment, 59 in each group were selected. The median time to recurrent biliary obstruction was not significantly different between the groups (p=0.46). In contrast, use of the 6-mm-diameter FCSEMS resulted in a significantly reduced incidence of stent-related adverse events (AEs) (p=0.016), especially cholecystitis (p=0.032), and patients aged <70 years were particularly affected by this significant reduction. Among the patients in the end-stage cohort who were unable to continue chemotherapy after FCSEMS deployment, the free rate of stent-related events, including recurrent biliary obstruction and stent-related AEs, was significantly higher in the 6-mm group (p=0.027). Conclusions For UR-MDBO, a 6-mm-diameter FCSEMS can be an optimal and safe option in the younger cohort with a relatively high risk of AEs and in the end-stage cohort requiring safer drainage without interference from stent-related events during times of poor prognosis.